Button Man - Gross, Andrew, 1952- (Thorndike, Maine : Center Point Large Print, 2019)
"Following up The One Man and The Saboteur, Grosss next historical thriller brings to life the drama of the birth of organized crime in 1930s New York City from the tale of one family"--
Keywords: Jewish families -- New York (State); New York; Fiction; Organized crime -- New York (State); New York; Fiction; New York (N.Y.) -- Social life and customs -- 20th century; Fiction; Domestic fiction; Historical fiction; Domestic fiction; Fiction; Historical fiction